Preliminary study toward standardization of tomato-mango jam blend - Barrios , Aimee Dalumpines (2001.)
Three different product formulations of T-M jam blends were prepared varying ratios of ripe tomato to mango pulps, namely: A, B and C.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tomato-mango jam